An Alternative Surgical Procedure for a Patient with Critically Restenosed and Kinked Carotid Artery: Graft Interposition - Haydar Yaşa; Övünç Aslan; Barçın Özcem; Muhammet Akyuz; Ali Gürbüz; Galip Akhan (Case Reports in Surgery)
According to the literature data, the prevalence of restenosis after carotid endarterectomy ranges between 6 and 36%. The etiological factor is intimal hyperplasia for early period, whereas it is atherosclerosis for late period. A 67-year-old male patient admitted to our clinic with a history of headache and minor stroke. His medical history was significant for right carotid endarterectomy 8 years ago. Recent Doppler ultrasound and digital substraction angiography revealed 75% stenosis and kinking corresponding to the segment distal to the endarterectomy region. Surgical endarterectomy is the treatment of choice in critical carotid stenosis. Endovascular therapy is primarily considered for patients if there is restenosis after carotid endarterectomy. However, the treatment modality is controversial in cases with concomitant carotid stenosis and kinking of internal carotid artery. We present our surgical approach to a case with significant stenosis and kinking of internal carotid artery. We performed a 6-mm-PTFE graft interposition between common and internal carotid artery and resection of the kinking segment.